Engaging and partnering with Aboriginal and Torres Strait Islander parents and caregivers - Simone White; Peter Anderson; Graeme Gower; Matt Byrne; Maria Bennett; Alison Quin; Anna Darling (2019)
The Engaging and partnering with Aboriginal and Torres Strait Islander parents and caregivers two-year project has culminated in a unique interactive website (see www.yourstoryourjourney.net) that houses a number of learning and teaching tools, strategies and resources designed to support all those working to improve the educational success of Aboriginal and Torres Strait Islander students in schools, Australia’s First Nations peoples. It is intended to be used in teacher education programs (pre-service and in-service), by teachers and school leaders, and by Aboriginal and Torres Strait Islander communities. The resource has been created to help all educators form relationships and partnerships with local communities, parents and caregivers to achieve better educational outcomes for all Aboriginal and Torres Strait Islander students. The resource positions educators as powerful agents of change. The project began from the premise that school education has traditionally involved ways of thinking and learning imposed on Aboriginal and Torres Strait Islander people, more often than not with little to no opportunity for input or collaboration. This lack of recognition and involvement has to date served only to continue the silencing of Aboriginal and Torres Strait Islander peoples’ voices that lies at the centre of our nation’s history, and impedes real progress towards reconciliation (Uluru Statement from the Heart, 2017). The need to address this issue and work instead to privilege and honour Aboriginal and Torres Strait Islander peoples’ experiences and knowledges, ensuring they are at the centre of the embodied enactment of schooling in every community, has been (and will continue to be), at the very heart of this project and has guided the project at all stages of its development.